The Effects of Opioid Use during Pregnancy on Infant Health and Well-Being. Issue 1 (September 2022) - Pac, Jessica; Durrance, Christine; Berger, Lawrence; Ehrenthal, Deborah B.
We estimate the causal effects of infants' exposure to opioids in utero on their health at birth and on the likelihood that their parents will be the subjects of subsequent reports to child protective services. We use administrative data on 259, 723 infants born to 176, 224 mothers enrolled in Medicaid between 2010 and 2019. Results suggest that an infant experiencing withdrawal symptoms after birth or needing admission to intensive care is strongly associated with prenatal opioid exposure, and that this effect is concentrated among those whose mothers used illicit opioids or were undergoing medication-assisted opioid treatments in their first and third trimesters. Prenatal opioid exposure is also associated with referrals of parents to child protective services and with being born preterm, low birthweight, or small for gestational age. We find smaller effects among infants exposed to prescription opioids, but these effects are not trivial, supporting current recommendations to balance the potential for infant adverse effects with the benefits of pain management during pregnancy.